Evaluation of the learning implementation of technopreneur profile elements in the subject of fundamentals of fashion skills based on the independent curriculum in Vocational High Schools - Kusumadewi, Putu Diah Ari; Wening, Sri (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2024)
This study aims to evaluate the implementation of technopreneur profile element learning in the primary subject of fashion skills based on the independent curriculum at SMK Negeri 1 Wonosari and SMK Negeri 6 Yogyakarta in terms of planning (antecedent), process (transaction), results (output). This research is evaluation research using the Countenance evaluation model of Stake. The study population consisted of 2 teachers and 180 students in phase E of Fashion Design at SMK Negeri 1 Wonosari and SMK Negeri 6 Yogyakarta. Data collection techniques used are documentation and questionnaires. The results showed that: (1) The antecedent aspect of the implementation of technopreneur profile element learning at SMK is in the very good category (100%), planning the flow of learning objectives (ATP) shows the very good category (100%), as well as planning the teaching module shows a very good category (100%); (2) The transaction aspect of the technopreneur profile element of learning at SMK is in a good category (70%), the implementation of learning shows the good category (63%), and the learning assessment shows the good category (43%); (3) The output aspects of the technopreneur profile element of learning at SMK found that students from both schools succeeded in achieving the minimum completeness criteria with a percentage of 100%. Achievement of the learning objectives of the technopreneur profile at SMK Negeri 1 Wonosari & SMK Negeri 6 Yogyakarta was measured by test and non-test assessments.